2021
DOI: 10.3390/ani11113194
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin Regulates Epithelial Barrier Function of Mammary Glands in Dairy Cows

Abstract: Epithelial barrier function in the mammary gland acts as a forefront of the defense mechanism against mastitis, which is widespread and a major disorder in dairy production. Chemerin is a chemoattractant protein with potent antimicrobial ability, but its role in the mammary gland remains unelucidated. The aim of this study was to determine the function of chemerin in mammary epithelial tissue of dairy cows in lactation or dry-off periods. Mammary epithelial cells produced chemerin protein, and secreted chemeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The treatment of MAC-T cells with chemerin caused an increased expression of genes involved in milk protein synthesis, glucose uptake, and fatty acid synthesis, suggesting that chemerin may regulate the process of milk synthesis in the bovine mammary gland [18]. In another study, Suzuki et al [19] demonstrated that chemerin supports bovine MEC growth and epithelial barrier function and is strongly regulated by inflammatory stimuli, such as TNFα.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of MAC-T cells with chemerin caused an increased expression of genes involved in milk protein synthesis, glucose uptake, and fatty acid synthesis, suggesting that chemerin may regulate the process of milk synthesis in the bovine mammary gland [18]. In another study, Suzuki et al [19] demonstrated that chemerin supports bovine MEC growth and epithelial barrier function and is strongly regulated by inflammatory stimuli, such as TNFα.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in recent years revealed that chemerin may be one of the essential adipokines regulating the development and function of the mammary epithelium [18,19]. Chemerin, also known as retinoic acid receptor responder protein 2 (RARRES2), or tazaroteneinduced gene 2 protein (TIG2), is a 16 kDa chemoattractant cytokine (chemokine) secreted mainly by white adipose tissue [20].…”
Section: Introductionmentioning
confidence: 99%
“…The mammary gland adipose tissue provides a local source of fatty acids and metabolites for MEC [13]. The indirect regulation of the mammary epithelium by adipocytes is connected with their high secretory activity and local production of adipokines, such as leptin, adiponectin, chemerin, vascular endothelial growth factor (VEGF), interleukin 6 (IL-6), or tumor necrosis factor alpha (TNF-α) [13][14][15][16][17]. Deficiency in leptin signaling caused by loss of function mutation in the leptin gene causes defective mammary development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the MAC-T is one of the most often used immortalized bovine mammary epithelial cell lines to study bovine mammary gland functions, such as cell proliferation and apoptosis, tight junction permeability, inflammations, etc. [20][21][22][23]. Therefore, the objective of the current study was to investigate the effects of 5-HT on global gene expression profiles of bovine mammary epithelial cells by applying transcriptome analysis in MAC-T cells.…”
Section: Introductionmentioning
confidence: 99%